Internet Of Things Based Car Parking Monitoring Device Integrated with WEB Server - Alvin Indra Pratama; Elsyea Adia Tunggadewi; Winarno (IJCONSIST JOURNALS, 2025)
The rapid increase in the number of vehicles has intensified the need for an efficient and well-managed parking system. Conventional parking systems, which rely heavily on human attendants, often suffer from the absence of real-time monitoring, resulting in congestion and operational inefficiencies. This research proposes an Internet of Things (IoT)-based Smart Parking System employing the HC-SR04 ultrasonic sensor to detect vehicle presence in each parking slot. The system is integrated with a web server that enables real-time monitoring and provides recommendations for parking slot based on proximity to entrance. The implementation utilizes ESP32 microcontrollers to process sensor data and communicate with the web server. All sensor readings are stored in a MySQL database and accessed through a PHP-based web application. Experimental evaluation demonstrates a 100% accuracy rate in slot detection, response time, and recommendation performance. The proposed system significantly enhances parking management efficiency and minimizes fuel consumption by reducing the time required to locate available parking spaces.